Molecular cloning of rat homologues of the Drosophila melanogaster dunce cAMP phosphodiesterase: evidence for a family of genes. - Swinnen, J V (1989)
To study the structure and function of cyclic nucleotide phosphodiesterases (PDEs) involved in mammalian gametogenesis, a rat testis cDNA library was screened at low stringency with a cDNA clone coding for the Drosophila melanogaster dunce-encoded PDE as a probe. This screening resulted in the isolation of two groups of cDNA clones, differing in their nucleotide sequences (ratPDE1 and ratPDE2). In the rat testis, RNA transcripts corresponding to both groups of clones were expressed predominantly in germ cells. Additional screenings of a Sertoli cell cDNA library with a ratPDE2 clone as a probe led to the isolation of two more groups of clones (rat-PDE3 and ratPDE4). Unlike ratPDE1 and ratPDE2, these clones hybridized to transcripts present predominantly in the Sertoli cell. In the middle of the coding region, all four groups of clones were homologous to each other. The deduced amino acid sequences of part of this region were also homologous to the D. melanogaster dunce PDE and to PDEs from bovine and yeast. These data indicate that a family of genes homologous to the D. melanogaster dunce-encoded PDE is present in the rat and that these genes are differentially expressed in somatic and germ cells of the seminiferous tubule. These findings provide a molecular basis for the observed heterogeneity of cAMP PDEs.